1999
DOI: 10.1523/jneurosci.19-12-04972.1999
|View full text |Cite
|
Sign up to set email alerts
|

Impairments in High-Frequency Transmission, Synaptic Vesicle Docking, and Synaptic Protein Distribution in the Hippocampus of BDNF Knockout Mice

Abstract: Brain-derived neurotrophic factor (BDNF) promotes long-term potentiation (LTP) at hippocampal CA1 synapses by a presynaptic enhancement of synaptic transmission during highfrequency stimulation (HFS). Here we have investigated the mechanisms of BDNF action using two lines of BDNF knockout mice. Among other presynaptic impairments, the mutant mice exhibited more pronounced synaptic fatigue at CA1 synapses during high-frequency stimulation, compared with wild-type animals. Quantitative analysis of CA1 synapses r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
343
1
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 429 publications
(368 citation statements)
references
References 57 publications
20
343
1
2
Order By: Relevance
“…Moreover, chronic treatment with FLX promotes BDNF expression in the rat hippocampus (De Foubert et al, 2004) that in turn leads to activation of genes and biochemical pathways involved in plasticity and survival (Mattson et al, 2004). At synaptic structural level, adult BDNF knockout mice show reduced number of vesicles docked at presynaptic active zones and marked decreased levels of SYN and synaptobrevin (Pozzo-Miller et al, 1999), alterations that can be reversed by BDNF administration (Pozzo-Miller et al, 1999), and somewhat resemble the synaptic protein decrease we observed in LH animals. On the other hand, Figure 7 Persistence of NLF diminution after fluoxetine (FLX) withdrawal.…”
Section: Flx-induced Synaptic Remodeling and Behavioral Responsesupporting
confidence: 54%
See 1 more Smart Citation
“…Moreover, chronic treatment with FLX promotes BDNF expression in the rat hippocampus (De Foubert et al, 2004) that in turn leads to activation of genes and biochemical pathways involved in plasticity and survival (Mattson et al, 2004). At synaptic structural level, adult BDNF knockout mice show reduced number of vesicles docked at presynaptic active zones and marked decreased levels of SYN and synaptobrevin (Pozzo-Miller et al, 1999), alterations that can be reversed by BDNF administration (Pozzo-Miller et al, 1999), and somewhat resemble the synaptic protein decrease we observed in LH animals. On the other hand, Figure 7 Persistence of NLF diminution after fluoxetine (FLX) withdrawal.…”
Section: Flx-induced Synaptic Remodeling and Behavioral Responsesupporting
confidence: 54%
“…At this level, experimental evidences point out once again to BDNF as an appealing candidate. Besides its role in synaptogenesis Hu et al, 2005) and synaptic ultra structural composition (Pozzo-Miller et al, 1999;Tartaglia et al, 2001;Tyler and Pozzo-Miller, 2001;Carter et al, 2002) in developing and adult brain, this neurotrophin promotes synaptic connectivity by modulating maturation of developing synapses in culture (Collin et al, 2001) and by stabilizing in vivo synapses already established (Hu et al, 2005). Taken into account that BDNF has been proposed to mediate FLX action, it can be hypothesized that antidepressant withdrawal might drop down BDNF levels to the abnormally low concentrations described in stressed animals leading to the reversion of synaptic changes we observed under FLX treatment.…”
Section: Synaptic Plasticity and Recurrence Of Despaired Behavior Aftmentioning
confidence: 71%
“…Consistent with these observations, several groups report that BDNF treatment of hippocampal and cortical neuronal cultures increase synaptobrevin expression (Takei et al, 1997;Tartaglia et al, 2001;Yamada et al, 2002). In accordance with the effects of exogenous neurotrophins, mice that are deficient in either BDNF or TrkB exhibit marked reductions in the total number of docked vesicles at hippocampal synapses and a redistribution of docked vesicles to areas far from the active zone in the cerebellar synapses (Martinez et al, 1998;Pozzo-Miller et al, 1999;. Moreover, hippocampal sections from TrkB-deficient mice exhibit an overall reduction in syntaxin 1 and SNAP25 immunoreactivity (Martinez et al, 1998).…”
Section: Neurotrophins As Synaptic Modulators: Presynaptic Terminal Fmentioning
confidence: 63%
“…At hippocampal and cortical synapses in vivo and in vitro, BDNF facilitates long-term potentiation, attenuates long-term depression and promotes homeostatic and competitive interactions that refine neural circuitry (Korte et al, 1995;Akaneya et al, 1996;Cabelli et al, 1996;Huang et al, 1999;Turrigiano and Nelson, 2000;Turrigiano and Nelson, 2004). At hippocampal and cerebellar synapses in BDNF-deficient mice, high-frequency stimulation and paired-pulse facilitation are impaired, which is consistent with compromised presynaptic release (Pozzo-Miller et al, 1999;Carter and Regehr, 2002). These studies demonstrate that BDNF acts presynaptically to modulate the dynamics of glutamate release at developing and mature synapses.…”
Section: Neurotrophins As Synaptic Modulators: Presynaptic Terminal Fmentioning
confidence: 80%
See 1 more Smart Citation